Causes of Dropout from immunization among children in two selected slum area of Dhaka City (East West Medical College Journal, 2024)
This study will contribute information that can be used by policymakers in the Ministry of Health (MOH) to create policies that will encourage mothers to complete their immunization schedule among children in Bangladesh. It will benefit health workers like nurses, doctors or clinicians by giving useful data on the factors associated with immunization dropout among children of one month to 18 months of age in Bangladesh. Materials and Methods: A cross-sectional household survey was conducted in two selected slum area in Dhaka city and 120 married women (60 from each slum area of Dhaka city) were interviewed through face -to-face by the researcher. The target population was the parents had children of age from 1 month to 18 month and had routine child vaccination card were interviewed. The total sample size was 120 in number and they were selected by using systematic sampling technique. The study was based on primary data. The instruments of the study were pretested semi-structured questionnaire. After editing and coding the coded data enter into the computer SPSS Version 16.0 was used to analyze the data. Immunization was categorized into ‘complete’ and ‘drop-out’. Bivariate associations were then evaluate using Chi-square and spearman’s correlation. Logistic regression was finally performed to evaluate the strength of the predictive variables to immunization dropout. A confidence interval of 0.05 was considered in this study. Place and Period of the Study: Study was conducted from 8th January 2022 to 21th February 2022 in Tongi (Arshadnagor, Bank field, Hazi Mazar, Nishad Nagar slums -60 household) and Dhaka north City Corporation (korail slum from Banani -60 household). Results: Among the 120 participants majority that is 84.2% represented the age group of 21-35 years followed by 15.0% of